ANALISIS KOHESI DAN KOHERENSI RUBRIK OPINI SINYAL BAHAYA DARI SRI LANKA PADA MAJALAH TEMPO EDISI 27 APRIL 2019 - Ilham Fadli, Rusli; Nurul Afni, Fitri (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Discourse analysis is a study that examines or understands the meaning of a reading. Good discourse has a continuous unity between one and the other. To produce good structure and meaning in producing a discourse, there are important criteria in compiling the discourse. The preparation of good discourse must have coherence and cohesion used to create harmonious and mutually integrated readings. In this study, the author uses a pragmatic approach so that readers can understand clearly how important elements of cohesion and coherence exist in a sentence. The object of the research subject was the Hazard Signal opinion from Sri Lanka in Tempo magazine, April 27, 2019. Opinion "Danger Signals from Sri Lanka" in April 27, 2019 edition of Tempo, it can be concluded that the seven paragraphs are paragraphs that have good cohesion between words and sentences also have good coherence between sentences and between paragraphs. With the existence of coherence and cohesion in a discourse, the discourse will produce neat and easy to read reading